Congenital and acquired nonneoplastic adrenal diseases - Turgut, Ahmet T.; Onur, Mehmet Ruhi; Akpinar, Erhan; Dogra, Vikram S.; MacLennan, Gregory T. (Springer-Verlag London Ltd, 2013)
Widespread use of cross-sectional imaging has resulted in an increased incidence of detection of adrenal lesions. Congenital and acquired nonneoplastic disorders of the adrenal gland include congenital adrenal hyperplasia, adrenal cyst, adrenal cortical hyperplasia, adrenal hemorrhage, adrenal tuberculosis, adrenal histoplasmosis, adrenohepatic fusion, and adrenal trauma. In this chapter, the imaging features of congenital and acquired nonneoplastic diseases of the adrenal gland are described. © Springer-Verlag London 2013.